SISTEM PENDUKUNG KEPUTUSAN PENENTUAN BIJI KOPI BERKUALITAS DENGAN METODE ANALITYCAL HIERARCHY PROCESS (AHP) - UL Khairat; Muammar Muammar; Abidin Abidin (LPPM UNIVERSITAS BINA INSAN, 2021)
Quality is a factor that plays an important role in the world of trade. The better the quality of the commodity to be traded, the higher the amount of demand. Quality coffee beans in this case are commodities from agricultural products and coffee companies engaged in the trade world need good quality to remain competitive in the international trade market, the determination of quality coffee beans as a commodity requires a precision in the selection process, so that according to the needs expected by consumersThe decision of the company in determining the quality of coffee beans must be related as expected. In this case the method used is the Analytical Hierarchy Process (AHP). The AHP method is to determine the weight value for each criterion, the criteria in question are water content (%), dirt content (%), seed size (mm), seed color and Pests, then proceed with the ranking process that will select the coffee beans. Based on the description of the problem above, The system can collect data on the Criteria for Determining Quality Coffee Beans as well as Alternative and Comparative data can make decisions by calculating the value of each Criteria and Alternatives so that a Quality Coffee decision can be given.